3D BIM-enabled spatial query for retrieving property boundaries: a case study in Victoria, Australia. Issue 2 (1st February 2020) - Barzegar, Maryam; Rajabifard, Abbas; Kalantari, Mohsen; Atazadeh, Behnam
ABSTRACT: In the cadastral system of Victoria, the legal extent of properties is defined by a wide range of property boundaries referencing physical objects. These boundary types are typically represented in 2D plans. However, to address the challenges of 2D plans in complex buildings, there has been a growing trend towards the adoption of 3D models. These 3D models have been mainly used for visualization purposes, with no spatial query developed for identifying property boundaries in 3D models. Among 3D models, the Building Information Modelling (BIM) environment provides the potential capabilities for modelling property boundaries. In this paper, a spatial query approach predicated on topological relationships between a legal space and physical objects is developed to identify four types of property boundaries. A BIM model based on a case study in Victoria is used for implementation of the developed approach and the retrieved boundaries related to several properties with different levels of structural complexities are represented. In addition, various challenges during this process such as the impact of different design methods, and issues related to balconies and doors are discussed. The importance of this study is highlighted by a common scenario related to querying property boundaries.